2016
DOI: 10.1111/cid.12466
|View full text |Cite
|
Sign up to set email alerts
|

Autogenous bone grafting for treatment of osseous defect after impacted mandibular third molar extraction: A randomized controlled trial

Abstract: The result of this study demonstrated that scaling and root planning was beneficial to periodontal healing of M2 after impacted M3 extraction. Addition of autogenous bone grafting for the treatment of osseous defects distal to M2 was safe and more effective than periodontal treatment alone. (Registry Number: ChiCTR-IOC-15006561).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 35 publications
1
34
0
1
Order By: Relevance
“…3 The parameters representing new bone formation were highest in group Ta, which in accordance with the results of several studies 9,15,16 and proved again that the AB is the gold standard of bone grafting material. Until 12 weeks after surgery, conspicuous invagination remained still.…”
Section: Main Findingssupporting
confidence: 86%
See 4 more Smart Citations
“…3 The parameters representing new bone formation were highest in group Ta, which in accordance with the results of several studies 9,15,16 and proved again that the AB is the gold standard of bone grafting material. Until 12 weeks after surgery, conspicuous invagination remained still.…”
Section: Main Findingssupporting
confidence: 86%
“…It can be concluded that distal bone defect may lead to severe periodontal bone loss of the molar, and confirm the finding of our previous randomized controlled clinical study. 3 There is report in the literature that up to 65% resorption of the augmented AB in minipig maxillary sinus floor augmentation during the first 12 weeks. In group Ta, the sites displayed a normal morphology of bone and bone marrow, little AB particles could be identified, probably because of their rapid incorporation and subsequent resorption as part of the remodeling process.…”
Section: Main Findingsmentioning
confidence: 99%
See 3 more Smart Citations